Development of Interactive E-Modules on Plant Tissue Material to Improve Conceptual Understanding in Grade XI Students of Bandar Pulo High School, Batang Serangan District - Nadia Rahma; Khairuna Khairuna (Journal of Educational Sciences, 2026)
Students' limited conceptual understanding of Biology, particularly Plant Transportation as a subtopic of plant tissue, is often associated with the predominance of conventional teaching methods and the limited use of interactive learning media. The research employed a Research and Development (R&D) approach using the Four-D (4-D) model, consisting of the Define, Design, Develop, and Disseminate stages. Data were collected through observations, interviews, expert validation sheets, teacher and student response questionnaires, and pretest–posttest assessments. Qualitative and quantitative data were analyzed to determine the validity, practicality, and effectiveness of the developed e-module. The results showed that the e-module achieved a very valid category based on expert validation, with an overall validity score of 95.31%. Practicality testing also indicated excellent results, with teacher and student response scores of 93.75% and 96.73%, respectively. Furthermore, students' average scores increased from 58.25 on the pretest to 85.38 on the posttest, with an N-Gain of 0.64, indicating a moderate improvement in conceptual understanding. These findings demonstrate that the interactive e-module is valid, practical, and effective in enhancing students' conceptual understanding of Plant Transportation and can serve as an innovative learning resource for Biology instruction.